Evaluating a light‐louver system for behavioural guidance of age‐0 white sturgeon. (25th July 2017) - Ford, M.I.; Elvidge, C.K.; Baker, D.; Pratt, T.C.; Smokorowski, K.E.; Patrick, P.; Sills, M.; Cooke, S.J.
Abstract: Water diversions for hydropower and other applications are some of the most disruptive alterations affecting fish populations in lotic systems. Although many different strategies have been developed to reduce lethal encounters with such infrastructure, few studies have evaluated different forms of behavioural guidance concurrently. Here, we combine an LED‐based light guidance device (LGD) equipped with adjustable wavelength and strobing output with a reverse‐configured louver rack to assess the effectiveness of this two‐part behavioural guidance system on downstream movement through a bypass by age‐0 white sturgeon ( Acipenser transmontanus ). Several combinations of LGD and louver settings were tested under both simulated day and night (low light) conditions in a laboratory setting. In the absence of the LGD, louver slat spacings of 10 or 20 cm were most effective at achieving downstream bypasses with greater success rates ( two‐fold greater) under night conditions than under day conditions. Incorporating the LGD operating at the most attractive setting (green light strobing at 20 Hz) with the louver spacings of 10 or 20 cm achieved the highest rates of bypass usage (100% and 97%, respectively) under both day and night conditions while the control treatment (no LGD or louver) resulted in the lowest bypass rate (46%) among fish that moved downstream. Collectively, these results demonstrate that complementary cues can enhance the behavioural guidance of fishes and highlight the importance of continuing to explore the use of multiple strategies to mitigate entrainment for high priority fish species.